Explanatory model of behavioral adaptation in video game addiction among adolescents in urban and rural Peru: the mediating role of anxiety - Julio Cesar Huamani-Cahua; Estefany Ojeda-Flores; Norma Roxana Medina Arce; Leslie Emilia Villanueva Kuong; Michael Antony Ojeda-Flores (Frontiers in Psychology)
IntroductionThe study aimed to determine the relationships between behavioral adaptation and video game addiction, mediated by anxiety, in Peruvian adolescents from urban and rural areas, using a structural equation modeling (SEM) approach.MethodsThis explanatory and cross-sectional study employed convenience sampling, comprising 606 students of both sexes, aged 11 to 13, with 62.4% from urban areas and 37.6% from rural areas. The instruments used included the State-Trait Anxiety Inventory for Children (STAIC) to measure state and trait anxiety, the Behavioral Adaptation Inventory (IAC), and the Video Game Dependency Test (TDV). These instruments demonstrated adequate validity and reliability for the sample through confirmatory factor analysis (CFA), ensuring their relevance in the Peruvian context.ResultsThe SEM results confirmed that behavioral adaptation influences video game addiction, mediated by anxiety, with good model fit indices (χ2/df = 4.836; TLI = 0.945; CFI = 0.964; GFI = 0.950; RMSEA = 0.080, 90% CI [0.068, 0.092]). Regarding anxiety types, state anxiety showed a stronger negative mediating effect (β = −0.31; β = 0.20) compared to trait anxiety (β = −0.22; β = 0.16). Significant differences were found between rural and urban students, with rural adolescents exhibiting lower behavioral adaptation and higher levels of state and trait anxiety (p < 0.001) compared to their urban peers.DiscussionThe findings support theories emphasizing the interaction between emotional and behavioral factors in the development of problematic behaviors. Additionally, state anxiety is identified as having a greater mediating impact than trait anxiety, suggesting that situational emotional responses, rather than stable predispositions, are key determinants in intensifying addictive behaviors in specific contexts.